What do you call a group of alligators? : and other reptile and amphibian groups - Nathan, Emma. (Woodbridge, CT : Blackbirch Press, 2000)
Examines the habits of various reptiles and amphibians and explains what you call groups of them, such as a quiver of cobras, a bask of crocodiles, and a knot of toads.
Includes bibliographical references (p. 23) and index.
Science Books & Films (A.A.A.S.).
4.4.
4.4
3-6
Keywords: Amphibians -- Miscellanea -- Juvenile literature; English language -- Collective nouns -- Juvenile literature; Reptiles -- Miscellanea -- Juvenile literature; Amphibians -- Miscellanea; English language -- Collective nouns; Questions and answers; Reptiles -- Miscellanea; Amphibians -- Miscellanea; English language -- Terms and phrases; Reptiles -- Miscellanea